The effects of buffer condition on the fouling behavior of MVM virus filtration of an Fc‐fusion protein. Issue 10 (6th July 2019) - Namila, FNU; Zhang, Da; Traylor, Steven; Nguyen, Tung; Singh, Nripen; Wickramasinghe, Ranil; Qian, Xianghong
Abstract: A combined pore blockage and cake filtration model was applied to the virus filtration of an Fc‐fusion protein using the three commercially available filters, F‐1, F‐2, and F‐3 in a range of buffer conditions including sodium‐phosphate and tris‐acetate buffers with and without 200 mM NaCl at pH 7.5. The fouling behaviors of the three filters for the feed solutions spiked with minute virus of mice were described well by this combined model for all the solution conditions. This suggests that fouling of the virus filters is dominated by the pore blockage mechanism during the initial stage of the filtration and transformed to the cake filtration mechanism during the later stage of the filtration. Both flux and transmembrane resistance can be described well by this model. The pore blockage rate and the rate of increase of protein layer resistance over blocked pores are found to be affected by membrane properties as well as the solution conditions resulting from the modulation of interactions between virus, protein, and membrane by the solution conditions. Abstract : A combined pore blockage and cake filtration model was applied to the virus filtration of an Fc‐fusion protein using the three commercially available filters, F‐1, F‐2, and F‐3 in a range of buffer conditions including sodium‐phosphate and tris‐acetate buffers with and without 200 mM NaCl at pH 7.5.